ANTIBACTERIAL AND ANTIFULGAL ACTIVITIES OF COBAL AND NICKEL COMPLEXEXES OF SHIFF BASE - Uba, Bala; Tukur, Y (FUDMA Journal of Sciences, 2026)
Schiff base complexes of cobalt and nickel were synthesized through a condensation reaction between salicylaldehyde and 2-amino-3-methylpyridine in the presence of the metal chlorides of Co(II) and Ni(II). The compounds were characterized using melting point/decomposition temperature, solubility, magnetic measurements, conductivity, FT-IR, and elemental analysis. Orange-yellow, dark blue, and brown colours were observed for the Schiff base and its complexes. Melting point/decomposition temperatures of 120°C, 212°C, and 222°C were recorded. Both the Schiff base and the metal complexes were soluble in water, methanol, ethanol, and DMSO, but only slightly soluble in other solvents. The electrical conductivity values obtained were 16.5 and 10.7 Ω⁻¹ cm² mol⁻¹, indicating that the synthesized complexes are non-electrolytes. Effective magnetic moments of 3.9 BM and 1.28 BM suggest an octahedral geometry for the complexes. The IR spectrum revealed a band at 1581 cm⁻¹, indicating the formation of the azomethine (C=N) group and confirming the formation of the Schiff base. This band shifted to higher frequencies, 1610 cm⁻¹ and 1618 cm⁻¹, indicating complex formation. Bands observed at 755 cm⁻¹ for M–N and 618 cm⁻¹ for M–O in the spectra of the complexes support coordination of the Schiff base to the respective metals. The CHN elemental analysis data showed good agreement between the experimental and calculated values, suggesting a 1:2 metal-to-ligand ratio.
Keywords: Metals Complexes antibacterial; antifungal; Schiff base